Predicting early lethal outcome after acute ischemic supratentorial stroke using clinical parameters and parameters of quantitative electroencephalography - Kozyolkin, O.; Kuznietsov, A. A.; Козьолкін, Олександр Анатолійович; Кузнєцов, Антон Анатолійович (Запорізький державний медичний університет, 2015)
Background: Elaboration of statistical models to predict early lethal outcome (ELO) after acute ischemic supratentorial stroke (AISS) is a very important and relevant in modern angioneurology that can help the practicioners to improve treatment approaches. We therefore developed new model using clinical parameters and parameters of quantitative electroencephalography (QEEG).